Experiencias de investigación-acción sobre el aprendizaje por descubrimiento de los circuitos eléctricos - Martín Muñoz, A.; Muñoz Arrabal, T.; Rodríguez Cardeña, A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
Three experiences on the learning of electric circuits are presented through analysis of those psychopedagogical aspects of learning wich are most relevant in the building of the children's scientific thinking.